Genetic Meningococcal Antigen Typing System (gMATS): A genotyping tool that predicts 4CMenB strain coverage worldwide - Muzzi, Alessandro; Brozzi, Alessandro; Serino, Laura; Bodini, Margherita; Abad, Raquel; Caugant, Dominique; Comanducci, Maurizio; Lemos, Ana Paula; Gorla, Maria Cecilia; Křížová, Pavla; Mikula, Claudia; Mulhall, Robert; et al. (Vaccine, 2019)
BACKGROUND: The Meningococcal Antigen Typing System (MATS) was developed to identify meningococcus group B strains with a high likelihood of being covered by the 4CMenB vaccine, but is limited by the requirement for viable isolates from culture-confirmed cases. We examined if antigen genotyping could complement MATS in predicting strain coverage by the 4CMenB vaccine. METHODS: From a panel of 3912 MATS-typed invasive meningococcal disease isolates collected in England and Wales in 2007-2008, 2014-2015 and 2015-2016, and in 16 other countries in 2000-2015, 3481 isolates were also characterized by antigen genotyping. Individual associations between antigen genotypes and MATS coverage for each 4CMenB component were used to define a genetic MATS (gMATS). gMATS estimates were compared with England and Wales human complement serum bactericidal assay (hSBA) data and vaccine effectiveness (VE) data from England. RESULTS: Overall, 81% of the strain panel had genetically predictable MATS coverage, with 92% accuracy and highly concordant results across national panels (Lin's accuracy coefficient, 0.98; root-mean-square deviation, 6%). England and Wales strain coverage estimates were 72-73% by genotyping (66-73% by MATS), underestimating hSBA values after four vaccine doses (88%) and VE after two doses (83%). The gMATS predicted strain coverage in other countries was 58-88%. CONCLUSIONS: gMATS can replace MATS in predicting 4CMenB strain coverage in four out of five cases, without requiring a cultivable isolate, and is open to further improvement. Both methods underestimated VE in England. Strain coverage predictions in other countries matched or exceeded England and Wales estimates.
Keywords: Antigens, Bacterial; Genotyping Techniques; genotypizační techniky; Global Health; meningokokové vakcíny; Meningococcal Vaccines; molekulární epidemiologie; celosvětové zdraví; Humans; genotyp; Neisseria meningitidis, Serogroup B; Molecular Epidemiology; Genotype; Neisseria meningitidis séroskupiny B; Meningitis, Meningococcal; antigeny bakteriální; lidé; meningokoková meningitida